Influence Communication, Work and Discipline of the education level on employee performance at PT. Fruit Oil (SBS) District. Kinali, Kab. West Pasaman - Fauzan, Fauzan; Sari, Mareta Kemala; Utami, Hayu Yolanda (Pendidikan Ekonomi, 2014)
ABSTRACT The formulation of the issues raised in this study is